Optimal discharge planning for esophagectomy patients with enhanced recovery after surgery: Recommendations - Li, Kunzhi; Wang, Kangning; Wei, Xing; Leng, Xuefeng; Fang, Qiang (Frontiers in Surgery, 2023)
Background: Studies have suggested that the postoperative length of stay (PLOS) of esophagectomy patients under the enhanced recovery after surgery (ERAS) pathway should be >10 days as against the previously recommended 7 days. We investigated the distribution and influencing factors of PLOS in the ERAS pathway in order to recommend an optimal planned discharge time. Methods: This was a single-center retrospective study of 449 patients with thoracic esophageal carcinoma who underwent esophagectomy and perioperative ERAS between January 2013 and April 2021. We established a database to prospectively document the causes of delayed discharge. Results: The mean and median PLOS were 10.2 days and 8.0 days (range: 5–97), respectively. Patients were divided into four groups: group A (PLOS ≤7 days), 179 patients (39.9%); group B (8 PLOS ≤10 days), 152 (33.9%); group C (11 PLOS ≤14 days), 68 (15.1%); group D (PLOS >14 days), 50 patients (11.1%). The main cause of prolonged PLOS in group B was minor complications (prolonged chest drainage, pulmonary infection, recurrent laryngeal nerve injury). Severely prolonged PLOS in groups C and D were due to major complications and comorbidities. On multivariable logistic regression analysis, open surgery, surgical duration >240 min, age >64 years, surgical complication grade >2, and critical comorbidities were identified as risk factors for delayed discharge. Conclusions: The optimal planned discharge time for patients undergoing esophagectomy with ERAS should be 7–10 days with a 4-day discharge observation window. Patients at risk of delayed discharge should be managed using a PLOS prediction model.